TEKNOLOGI PENURUNAN KADAR Fe AIR SAWAH PASANG SURUT MELALUI PENGGUNAAN BIOFILTER PURUN TIKUS (Eleocharis dulcis) - Ani Susilawati; Linda Indrayati (BERITA BIOLOGI, 2016)
Water management in acid sulfate soil can increase the productivity of land and crops, but the element of poison leaching into drainage channels gives negative impact on the environment. One approach to improve water quality is to filter or absorb the poison element. Purun tikus (Eleocharis dulcis) can act as a biofilter to improve water quality. The purpose of this study is to get biofilter technology (purun tikus) to reduce the levels of Fe, SO4 and increase the pH of the water. The experiment was conducted in greenhouse of Indonesian Swampland Agriculture Research Institute, Banjarbaru, South Kalimantan. Treatment was arranged in a factorial randomized block design with three replications.The first factor was the density of the biofilter ,consisted of: 1) 25%, 2) 50%, and 3) 100%, The second factor was the length of contact of water with biofilter that consisted of: 1). 12 hours, 2) 24 hours, and 3) 36 hours. The results showed that the density of purun tikus 50% in greenhouse experiments can decreased the concentration of Fe at 76.5%.